The dangerous rise of therapeutic education - Ecclestone, Kathryn (Routledge, 2009)
The silent ascendancy of a therapeutic ethos across the education system and into the workplace demands a book that serves as a wake up call to everyone. Kathryn Ecclestone and Dennis Hayes' controversial and compelling book uses a wealth of examples across the education system, from primary schools to university, and the workplace to show how therapeutic education is turning children, young people and adults into anxious and self-preoccupied individuals rather than aspiring, optimistic and resilient learners who want to know everything about the world. Â The chapters address a variety of thought-provoking themes, including how therapeutic ideas from popular culture dominate social thought and social policies and offer a diminished view of human potential how schools undermine parental confidence and authority by fostering dependence and compulsory participation in therapeutic activities based on disclosing emotions to others how higher education has adopted therapeutic forms of teacher training because many academics have lost faith in the pursuit of knowledge how such developments are propelled by a deluge of political initiatives in areas such as emotional literacy, emotional well-being and the 'soft outcomes' of learning The Dangerous Rise of Therapeutic Education is eye-opening reading for every teacher, student teacher and parent who retains any belief in the power of knowledge to transform people's lives. Its insistent call for a serious public debate about the emotional state of education should also be at the forefront of the minds of every agent of change in society... from parent to policy maker